Recommendation of the Polish Prenatal Cardiology Society on the Regulation of the Polish Ministry of Health concerning competencies in fetal echocardiography (code 013) and fetal cardiology (code 021) - Respondek-Liberska, Maria; Murlewska, Julia; Wielgoś, Mirosław; Wiecheć, Marcin; Czajkowski, Krzysztof; Preis, Krzysztof; Świątkowska-Freund, Małgorzata; Mazela, Jan; Oszukowski, Przemysław; Krekora, Michał; Grzesiak, Mariusz; Maroszyńska, Iwona; et al. (Prenatal Cardiology, 2023)
The Polish Ministry of Health officially introduced a new list of 57 medical competencies in 2023. The list includes two new competencies: prenatal echocardiography (013) and prenatal cardiology (021). Therefore, the Polish Prenatal Cardiology Society presents the following consensus on differentiation between these competencies and screening fetal heart scan.